Strategi Dakwah Nabi Ibrahim dalam Perpektif Pembelajaran Saintifik - Qurrotul Ainiyah; Sulistiorini Sulistiorini (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2017)
Prophet Ibrahim is one of the prophets who received the title as Father of Tauhid who invites his people in seeking God by using the mind. The verses of the Qur’an that recount the incident include the letter of al-An’am: 75-79. In the Curriculum 2013 known scientific learning process that involves students directly, to perform Cognitive processes. This research focuses on the use of mind in the process of knowledge of God by the Prophet Ibrahim in the perspective of scientific learning. With the method of library research through the historical and descriptive approach in the results obtained that the Prophet Abraham used the mind as a tool to awaken his people to find the true God, through contemplation and thinking rationally, about who has created nature and its contents, which should be used as God’s worship. This process is also known in the 2013 Curriculum Science lesson. The process has stages as in the scientific learning phase. Namely there are activities as follows: observing, asking, experimenting, reasoning, and communicate, like in learning.